2017
DOI: 10.1155/2017/5801432
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation of Some Heavy Metals: Analysis and Comparison of Cyprinus carpio and Labeo rohita from Sardaryab, Khyber Pakhtunkhwa

Abstract: We examined and compared heavy metals bioaccumulation in Cyprinus carpio and Labeo rohita netted from Sardaryab, a tributary of River Kabul. By using atomic absorption spectrometry we assessed different organs including livers, gills, and muscles. Metals studied were chromium, iron, zinc, lead, and copper. Livers of both species showed higher concentrations of metals while muscles showed the least amount. Chromium and iron were the highly concentrated metals in the gills and livers of both species. A quantity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 19 publications
3
19
0
Order By: Relevance
“…For Cd and Pb, the levels in this study are in line with values reported by Yancheva et al [22] in muscle tissue of common carp from Topolnitsa reservoir in Bulgaria. For essential metals, our Cr values are in good agreement with results found in the muscle tissues of common carp from the uncontaminated fishponds in the Czech Republic [23] and Kabul River in Pakistan [24]. In contrast, our Zn values are lower than those reported by Yousafzai et al [24] and by Čelechovská et al [23] in muscle tissue of common carp from the Keban Dam Lake in Turkey and the fishponds in the Czech Republic, respectively.…”
Section: Trace Element and Pcb Concentrationssupporting
confidence: 91%
See 1 more Smart Citation
“…For Cd and Pb, the levels in this study are in line with values reported by Yancheva et al [22] in muscle tissue of common carp from Topolnitsa reservoir in Bulgaria. For essential metals, our Cr values are in good agreement with results found in the muscle tissues of common carp from the uncontaminated fishponds in the Czech Republic [23] and Kabul River in Pakistan [24]. In contrast, our Zn values are lower than those reported by Yousafzai et al [24] and by Čelechovská et al [23] in muscle tissue of common carp from the Keban Dam Lake in Turkey and the fishponds in the Czech Republic, respectively.…”
Section: Trace Element and Pcb Concentrationssupporting
confidence: 91%
“…For essential metals, our Cr values are in good agreement with results found in the muscle tissues of common carp from the uncontaminated fishponds in the Czech Republic [23] and Kabul River in Pakistan [24]. In contrast, our Zn values are lower than those reported by Yousafzai et al [24] and by Čelechovská et al [23] in muscle tissue of common carp from the Keban Dam Lake in Turkey and the fishponds in the Czech Republic, respectively. Regarding Cu concentrations, samples analysed in this study showed levels of the same order of magnitude of those reported for common carp from the Czech Republic [23] To safeguard public health, concentration standards in fish for some heavy metals have been established by the European Commission.…”
Section: Trace Element and Pcb Concentrationssupporting
confidence: 91%
“…Contamination of fish by heavy metals has become an important global issue because it presents a threat to fish and poses health risks to fish consumers [72]. Assessment of heavy metal bioaccumulation in fish species of different aquatic habitats is very important [73]. Assessment of heavy metal levels in fish tissues is essential for aquatic ecosystem management and human consumption of fish [74].…”
Section: Bioaccumulation Of Heavy Metals In Freshwater Fishmentioning
confidence: 99%
“…In today's world, alarming water pollution has become a major threat to the environment and has led to the development of new technologies to minimize the potential contaminants from the water bodies. Effluents from the mining industries, power generating industries, electronic industries and tanneries contain large amounts of heavy metals that pose a great risk to the surviving population in and around the water bodies (Liu et al 2012) and cause bioaccumulation in beings that ingest these waters directly or indirectly (Yousafzai et al 2017). Heavy metals such as uranium, mercury, chromium, arsenic, lanthanum, lead, cadmium and zinc are few of the commonly found metals that contaminate the water bodies (Boddu et al 2003;Tchounwou et al 2012).…”
Section: Introductionmentioning
confidence: 99%